Translation Issues and Strategies Applied in the Comic Adulthood is a Myth - I Gusti Ayu Mahatma Agung (Yayasan Visi Intan Permata, 2021)
This research aims to find out the translation issues in the comic book Adulthood is a Myth. The study focuses on the analysis of translation issues that might affect the translation process. In addition, it also aims to find out the strategies applied to translate the verbal message in the comic book. This study is conducted with a descriptive qualitative approach. The translation issues in the comic book were classified based on the theory proposed by Nurlaila et al. (2018). The translation strategies were analyzed by using the theory proposed by Celotti (2014). The result shows that there are eight translation issues found in this study. They are onomatopoeia, interjection, measurement unit terms, swearing expressions, speaking fluency disorder, slang words, abbreviation, and dialect. The translation strategies applied were cultural adaptation, deletion, and leaving the source language untranslated. Overall, the translator did an excellent job by choosing the proper translation strategies and using a suitable language style for the target readers. This research may serve as a reference for future studies in comic translation. Furthermore, it could also help translators in overcoming challenges in translating comic books.